The Effect of Robotics-Based Storytelling Activities on Primary School Students’ Computational Thinking - Karin Tengler; Oliver Kastner-Hauler; Barbara Sabitzer; Zsolt Lavicza (Education Sciences, 2021)
Robotics is needed as education keeps up with challenges students are facing in a technological environment. A long-term research project focuses on developing a feasible robotics-based learning environment that enables primary school teachers to introduce computer science education. This paper shows educational robotics combining storytelling to promote computational thinking through the method of Tell, Draw, and Code. The study was conducted via pre–post test, using the Beginners Computational Thinking test (BCTt), with third and fourth graders (N = 40) to determine if the integration of robotics-based storytelling activities enhances computational thinking skills. Results show that an increase in computational thinking is evident after the intervention is implemented. The approach of combining stories, texts, and literature with educational robotics seems to be a promising concept to equip students with the required skills.